2018
DOI: 10.1108/sef-01-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Retirement saving in the UK: a life-cycle analysis

Abstract: Purpose-This paper studies long term savings accumulation in the UK. We use crosssectional information from the extensive dataset of the Family Resources Survey to compare long term saving amongst different ethnic groups with our control group, the native population. We reflect on whether different groups are more likely to suffer poverty in retirement. Design / Methodology / Approach-In our analysis we apply the life cycle framework to explain saving profiles. This theoretical model has been used extensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The socio-demographic factors, psychological constructs, financial literacy, economic and circumstantial forces are important factors concerning women's financial planning for retirement (Kumar et al, 2019). Socio-economic factors are the key elements in determining whether individuals plan for retirement, when controlled for the differences in saving behaviour between ethnic minorities with considerable decrease in population (Adami et al, 2018). Besides, the government intervention programs increase in knowledge, positive changes in attitudes linked to retirement and an increase in retirement linked planning/ preparation behaviours across various demographic characteristics of employees (Franca et al, 2016).…”
Section: Demographic Variables and Rpbmentioning
confidence: 99%
“…The socio-demographic factors, psychological constructs, financial literacy, economic and circumstantial forces are important factors concerning women's financial planning for retirement (Kumar et al, 2019). Socio-economic factors are the key elements in determining whether individuals plan for retirement, when controlled for the differences in saving behaviour between ethnic minorities with considerable decrease in population (Adami et al, 2018). Besides, the government intervention programs increase in knowledge, positive changes in attitudes linked to retirement and an increase in retirement linked planning/ preparation behaviours across various demographic characteristics of employees (Franca et al, 2016).…”
Section: Demographic Variables and Rpbmentioning
confidence: 99%
“…Of those approaching pension age a third of the poorest people aged 50-70, are from BAME groups (Centre for Ageing Better, IPPR and UCL, 2020) older people from ethnic minority groups in the UK are more likely to live in poverty due to higher rates of unemployment, lower wages when of working age (Runnymede, 2013), low levels of education, part-time work and long spells of unemployment (Adami et al, 2018). People in later life from BAME backgrounds are also more likely to live in deprived neighbourhoods, with the oldest and poorest quality housing (Vernon, 2020:N.p).…”
Section: Ethnic Group Ethnic Group and Socio-economic Factorsmentioning
confidence: 99%
“…However, it is important to note that BAME groups are not homogeneous. Adami et al (2018) identified socio-economic differences, where Asian women, with high educational levels had relatively high rates of retirement saving, while Pakistani and Bangladeshi women were far less likely to be a position to save. Women from ethnic minority groups are at particular risk of financial insecurity in later life (Centre for Ageing Better and Resolution Foundation, 2017).…”
Section: Ethnicity and Employment Trajectories Including Exitmentioning
confidence: 99%
“…The household budget should be communicated with all the relevant staff. Under the WEE, controlling power of the income and expenditure of family members as well as controlling herself is a significant phenomenon of her empowerment (Deka, 2015;Domingo et al, 2015;Adami, Carosi, & Sharma, 2018). Therefore, based on the previous researchers' definitions and explanations, in the present research context, controlling the use of income and expenditure termed as; authority and willingness of poor rural women to control the over expenditure of their families with the purpose of using this resources to productive ways.…”
Section: Control Over the Use Of Income And Expendituresmentioning
confidence: 99%